2021
DOI: 10.1101/2021.01.21.427617
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic analysis of the septal peptidoglycan synthase FtsWI complex supports a conserved activation mechanism for SEDS-bPBP complexes

Abstract: SEDS family peptidoglycan (PG) glycosyltransferases RodA and FtsW require their cognate transpeptidases PBP2 and FtsI (class B penicillin binding proteins) to synthesize PG along the cell cylinder and at the septum, respectively. The activities of these SEDS-bPBPs complexes are tightly regulated to ensure proper cell elongation and division. In Escherichia coli FtsN switches FtsA and FtsQLB to the active forms that synergize to stimulate FtsWI, but the exact mechanism is not well understood. Previously, we iso… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The equilibrium between the conformations was suggested to be regulated by MreC (or other proteins) of the elongasome complex [62] . This same regulation was proposed recently for the bPBP:SEDS complex of the divisome, despite the very different regulatory proteins of the divisome compared to the elongasome [77] . We explored this hypothesis by modeling the sa PBP1: sa FtsW complex of S. aureus , using the crystal structure of the T. thermophilus PBP2:RodA (PDB code 6PL6) as the template, in a lipid bilayer membrane ( Fig.…”
Section: Resultssupporting
confidence: 82%
“…The equilibrium between the conformations was suggested to be regulated by MreC (or other proteins) of the elongasome complex [62] . This same regulation was proposed recently for the bPBP:SEDS complex of the divisome, despite the very different regulatory proteins of the divisome compared to the elongasome [77] . We explored this hypothesis by modeling the sa PBP1: sa FtsW complex of S. aureus , using the crystal structure of the T. thermophilus PBP2:RodA (PDB code 6PL6) as the template, in a lipid bilayer membrane ( Fig.…”
Section: Resultssupporting
confidence: 82%
“…Under these two conditions, nearly all FtsW molecules are engaged in sPG synthesis and hence exhibit only one slow-moving, active population on the sPG-track, identical to that of FtsN. Moreover, tracking of various mutant derivatives of FtsN revealed that the only domain required for the processive complex formation on the sPG-track is the Essential (E) domain, which is proposed to interact with the sPG synthesis machinery FtsWI, likely via the FtsQLB complex 15,16,18,19 . Most importantly, such a complex is crucial for activating and sustaining sPG synthesis in a processive manner, as a double point mutation that inactivates the E domain (WYAA) prevents formation of the processive complex and causes failure of cell division.…”
Section: Discussionmentioning
confidence: 99%
“…Other noteworthy divisome proteins include FtsA, which links FtsZ polymers to the membrane 12 , the core septal PG (sPG) synthase complex composed of the polymerase FtsW and transpeptidase FtsI 13,14 , and the FtsQLB complex, which regulates FtsWI activity 15,16 (also see reviews [5][6][7] ). According to current models, FtsN acts through FtsA in the cytoplasm and the FtsQLB complex in the periplasm to activate synthesis of sPG by the FtsWI synthase complex [15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…In current models, FtsN-mediated activation of FtsWI occurs through the FtsLB complex 28,29,31 . FtsLB is a heterotetramer consisting of two FtsL and two FtsB subunits, both of which are single-pass membrane proteins.…”
Section: Introductionmentioning
confidence: 99%